PENERAPAN TEKNIK MEMBACA RAMPAK BERBASIS IMAJI MENTAL DALAM PEMBELAJARAN MEMBACA PUISI NARATIF: Penelitian Eksperimen Kuasi Siswa SMPN 40 Bandung Kelas VIII Tahun Ajaran 2016/2017 - Makrus, Fikri Azis (2017)
Penelitian ini dilatarbelakangi oleh pengajaran puisi di sekolah yang menjumpai banyak kesulitan. Tidak jarang, para guru sastra sendiri cenderung menghindarinya karena merasa kesulitan untuk mengajarkannya. Di sisi lain, siswa pun merasakan hal yang sama. Bahasa puisi selintas memang kata-katanya sederhana, tetapi dirangkai dalam konteks yang tidak terduga, acuan yang kabur, ungkapan yang asing. Bahkan, tampak sebagai pernyataan yang kosong. Di samping itu, puisi itu sendiri memang cukup pelik dan kaya akan jenis dan maknanya. Oleh karena itu, hal yang perlu mendapat perhatian dalam pengajaran puisi di sekolah adalah bagaimana pemilihan bahan pengajaran dan penyajiannya (metode) di dalam kelas. Untuk memecahkan masalah tersebut, peneliti mengujicobakan sebuah teknik membaca rampak berbasis imaji mental. Penelitian ini dilakukan untuk mengetahui keefektifan teknik membaca rampak berbasis imaji mental dalam pembelajaran membaca puisi naratif. Adapun rumusan masalah dalam penelitian ini adalah: 1) Bagaimanakah kemampuan membaca puisi naratif siswa kelas VIII SMPN 40 Bandung, sebelum menerapkan teknik membaca rampak berbasis imaji mental pada kelas eksperimen dan kelas kontrol? 2) Bagaimanakah proses penerapan teknik membaca rampak berbasis imaji mental pada pembelajaran membaca puisi naratif siswa kelas VIII SMPN 40 Bandung di kelas eksperimen? 3) Apakah terdapat perbedaan yang signifikan kemampuan membaca puisi naratif siswa kelas VIII SMPN 40 Bandung antara kelas eksperimen dan kelas kontrol? Berdasarkan rumusan masalah tersebut, maka tujuan penelitian ini adalah untuk mengetahui: 1) kemampuan awal siswa kelas VIII SMPN 40 Bandung dalam membaca puisi naratif sebelum menggunakan teknik membaca rampak berbasis imaji mental; 2) bagaimana proses penerapan teknik membaca rampak berbasis imaji mental dalam pembelajaran membaca puisi naratif siswa kelas VIII SMPN 40 Bandung; dan 3) perbedaan dan kemampuan akhir siswa kelas VIII SMPN 40 Bandung dalam membaca puisi naratif setelah menggunakan teknik membaca rampak berbasis imaji mental di kelas eksperimen. Metode penelitian yang digunakan adalah eksperimen kuasi dengan menghadirkan kelas eksperimen dan kelas kontrol sebagai kelas pembanding, sehingga, sampel dalam penelitian ini berjumlah 65 siswa yang terbagi ke dalam 32 siswa pada kelas eksperimen dan 33 siswa kelas kontrol yang diambil secara acak. Berdasarkan hasil pengujian hipotesis dapat disimpulkan bahwa teknik membaca rampak berbasis imaji mental efektif diterapkan dalam pembelajaran membaca puisi naratif di dalam kelas. Hal tersebut juga dapat dibuktikan dari nilai rata-rata kemampuan posttest siswa dalam membaca puisi naratif di kelas eksperimen. Berdasarkan penelitian ini, teknik membaca rampak berbasis imaji mental dapat diterapkan dalam pembelajaran membaca puisi naratif di sekolah.----------This study is conducted based on the number of issues in teaching poetry in schools. Mainly, literary teachers per se tend to avoid those problems because they are encountered with some difficulties in teaching it. On the other hand, students feel the same way. Poetic languages, in a glance, indeed seem to be a simple word but those are, in fact, arranged in unpredicted contexts, vague references, and uncommon expressions. In fact, it appears as an empty statement. As a result, all those aforesaid factors put more complexity towards the students. In addition, poem it self is quite complicated and contains various types and meanings. Therefore, the things that need to be paid attention in teaching poetry in school is how to do the selection of teaching materials and presentations (methods) in the classroom. In order to deal with these problems, the researcher tested a rampak reading technique based on mental imagery. This study was conducted in order to identify the effectiveness of the rampak reading technique based on mental imagery in the learning of reading a narrative poetry. With respect to the research problems of this present study, it was formulated as follow: 1) How is the ability of the students in class VIII SMPN 40, Bandung in reading narrative poetry, before applying the rampak reading technique based on mental imagery in experimental class and control class? 2) How is the process of rampak reading technique based on mental imagery implemented in the learning of reading narrative poetry in class VIII SMPN 40 Bandung in the experimental class? 3) Is there a significant difference between experimental class and control class in terms of the ability of students in class VIII SMPN 40 Bandung in reading poetry?. Based on the formulation of the research problems, this study then aims to know. 1) the ability of the students in class VIII SMPN 40 Bandung in reading narrative poetry before applying the rampak reading technique based on mental imagery; 2) how is the process of applying rampak reading techniques based on mental imagery in reading reading narrative poetry of the students in class VIII SMPN 40 Bandung; and 3) the difference and ability of students in class VIII SMPN 40 Bandung in reading narrative poems after applying the rampak reading technique based on mental imagery in experimental class. The research method employed in this carried out study was a quasi experiment method by presenting the experiment class and control class as comparative classes. Therefore, 65 students were involved as samples in this study and this number of students was divided into 32 students in the experimental class and 33 students in the control class which then were taken randomly. Based on the results of the hypothesis testing, it can be concluded that the technique of reading rampak based mental imagery was effectively applied in learning reading narrative poetry in the classroom. It can also be proved from the average score of posttest students' ability in reading narrative poetry in the experimental class. Based on this present study, the rampak reading technique based on mental imagery can be applied in the learning of reading narrative poetry in schools.